â€œGalak SireutÃ´h, YÃ¶ SiribÃ©â€ for Speaking English Among the Student Teachers in Aceh - Usman, Jarjani; Risdaneva, Risdaneva (SCAD Independent, 2018)
â€œGalak sireutÃ´h, yÃ¶ siribÃ©â€ is a popular saying in Aceh, referred to the person who is anxious to do what he wants to. This study investigated the student teachersâ€™ anxiety felt when using English orally during their learning. Using the adapted questionnaires from Youngâ€™s (1990), that has been adapted by Occhipinti (2009), it involved 46 students undertaking English Speaking in a higher education in Lhokseumawe, Aceh. The results show that the majority of the students like English very much; however, they spent little time for using it orally, ranging from 1 to 8 hours per week. Most of them also affirmed that their English speaking ability is bad. It was also found that most of the students were highly anxious when speaking English with high self-exposure, but less anxious when engaging in collaborative activities and when given enough time to prepare what they talk. Yet, several students seem to have trait anxiety as they are highly anxious in most learning activities. Most were highly anxious for speaking English individually. This is likely influenced by their contextual, social and cultural factors, such as people in Aceh are known as communal rather than individualistic society.